Apartment prices, the business cycle and time on market: Evidence from Bucharest - Taltavull de La Paz, Paloma; McGreal, Stanley; Anghel, Ion; Ciora, Costin (International Journal of Strategic Property Management, 2025)
The issue of time on market (TOM) correlation with the sale price remains under-explored considering the importance and complexity of the housing market. This paper argues that TOM is influenced by variables other than transaction prices and tests the hypothesis that the business cycle is important in explaining the dynamics of TOM and driving transaction prices in the housing market. In testing this hypothesis, the paper investigates the role of transaction prices and TOM in the housing market in Bucharest, Romania using granular observations of 32,000 price listings over the period 2013–2017, a time-scale that captures the economic recovery phase following the global financial crisis. The analysis shows that spatial correlation is strong for TOM rather than weak and that reinforcing spatial effects evidenced among TOM in transactions of closed units would reflect the strong clustering in prices but are balanced in a type of (contrary sign) distribution effect that diminish the whole spatial impact in TOM in similar size, describing a corrective mechanism leading to a more balanced impact on TOM. Results show that GDP affects transaction prices pro-cyclically (0.062%) and with persistence (0.054%), while only GDP growth (the cycle) influences TOM (0.352%).